Spatio-temporal distribution of endophytes in tomato (Solanum lycopersicum) crop - SAIKIA, BANDANA; BHATTACHARYYA, ASHOK; BORA, POPY (The Indian Journal of Agricultural Sciences, 2022)
Endophytes considered another version of rhizosphere microbes, are associated with all types of plants. However, their population and diversity have greater consequences in terms of plant healthcare, the information on these is still little understood. Tomato growing areas covering 11 districts, representing four major agro-climatic regions of Assam were studied for spatio-temporal distribution of endophytes. A total of 177 bacterial endophytes and 57 fungal endophytes were isolated from tomato crop, out of which; 143, 51 and 40 isolates were obtained from roots, stems and leaves, respectively. The maximum of 112 endophytes were isolated during monsoon followed by 64 and 58 isolates, isolated during pre-monsoon and post-monsoon periods, respectively, indicating the rich diversity in bacterial and fungal endophytes of tomato crop. The maximum tissue colonization was observed in roots followed by leaves and stems in decreasing order, with Bacillus sp. amongst bacterial isolates and Trichoderma sp. amongst fungal isolates. These observations on spatio-temporal distribution of bacterial and fungal endophytes suggested their potential habitat and suitable time of studying endophytes for better healthcare of tomato crop.